2011
DOI: 10.3409/fb59_1-2.59-64
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Steroidogenic Activity of the Granulosa Layer of F1 Preovulatory Ovarian Follicles of the Hen (Gallus domesticus)

Abstract: WOJTYSIAK D., OKÓLSKI A., SECHMAN A. 2011. Structure and steroidogenic activity of the granulosa layer of F1 preovulatory ovarian follicles of the hen (Gallus domesticus). Folia biologica (Kraków) 59: 59-64. The study was performed to determine the structure and steroidogenic activity of granulosa cells derived from the germinal disc region, proximal region and distal region of the largest preovulatory ovarian follicle (F1) of the hen. The study was carried out on 34 Hy-Line Brown egg-laying hens aged 40 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The cell layers are primarily responsible for the transport of nutrients, mechanical support of growing oocytes, and the biosynthesis of steroids, which are important for regulating the rapid growth of follicles (Guraya, 1989;Wojtysiak et al, 2011;Rodler and Sinowatz, 2013). Recent data have further confirmed that the follicle wall secretes immunity peptides (Abdelsalam et al, 2010) and determines the fate of follicles, advancing in development or undergoing atresia (Quirk et al, 2004).…”
Section: Q2mentioning
confidence: 88%
“…The cell layers are primarily responsible for the transport of nutrients, mechanical support of growing oocytes, and the biosynthesis of steroids, which are important for regulating the rapid growth of follicles (Guraya, 1989;Wojtysiak et al, 2011;Rodler and Sinowatz, 2013). Recent data have further confirmed that the follicle wall secretes immunity peptides (Abdelsalam et al, 2010) and determines the fate of follicles, advancing in development or undergoing atresia (Quirk et al, 2004).…”
Section: Q2mentioning
confidence: 88%
“…All elements of the follicular wall undergo obvious structural changes during the phase of growth when observed under an electron microscope (KOVASC et al 1992;MADEKUROZWA & KIMARO 2006). The normal maturation process of the oocyte within the ovarian follicle depends on the coordinated development of the follicular wall inducing granulosa and theca cells under the influences of various hormones and growth factors (WOJTYSIAK et al 2011;LIN et al 2011;HRABIA et al 2008;ONAGBESAN et al 2009;SECHMAN 2013). The reproductive axis hormone, follicle-stimulating hormone (FSH), plays a pivotal role in the process of follicular development.…”
mentioning
confidence: 99%
“…All these circumambient structures constitute the follicle wall. It can provide mechanical support and transport nutrients for the growing oocytes and play a key role in the synthesis of steroid hormones (WOJTYSIAK & KAPKOWSKA 2005;HERNANDEZ & BAHR 2003;WOJTYSIAK et al 2011), and it can also play important roles for the development of the oocyte and ovulation. All elements of the follicular wall undergo obvious structural changes during the phase of growth when observed under an electron microscope (KOVASC et al 1992;MADEKUROZWA & KIMARO 2006).…”
mentioning
confidence: 99%
“…Moreover, host genes of DE circRNAs were enriched in ovarian steroidogenesis, as well as MAPK signalling, prolactin signalling and PI3K-Akt signalling pathways. Previous studies concluded that ovarian steroidogenesis is important for GC differentiation and follicle development [12,[34][35]. MAPK signalling prevents premature differentiation of the granulosa layer within prehierarchical follicles [36], which is involved in the regulation of follicle growth.…”
Section: Discussionmentioning
confidence: 99%